Sexual orientation, entrepreneurship, and firm survival - Mikaela Backman; Christopher S. Carpenter; Erwan Dujeancourt; Samuel Mann (Small Business Economics, 2024)
We provide new evidence on sexual orientation, entrepreneurship, and firm survival using Swedish population register data linked to business registry data from 1995 to 2020. Over this period, we study over 19,000 individuals who ever entered a legal same-sex union and compare their entrepreneurship and firm level outcomes with individuals exclusively in different-sex unions. We find that sexual minority men are 7.8% less likely than comparable heterosexual men to be entrepreneurs, while sexual minority women are 4.8% more likely than comparable heterosexual women to be entrepreneurs. Both differences are statistically significant. We also provide the first evidence regarding the survival of sexual minority founded firms compared to firms founded by heterosexual individuals. Our results show that firms founded by sexual minority women fail more quickly than observably similar firms founded by heterosexual women, with no significant survival difference observed for sexual minority men. We explore the role of several external and internal factors that may explain these underlying patterns and find that lack of a `trapped market' may contribute to the higher failure rate of firms founded by sexual minority women. We also find suggestive support for a role of romantic partners in explaining differences in firm survival experienced by sexual minority women compared to heterosexual women. -
Keywords: J15; J22; L26; 330; Sexual orientation; Entrepreneurship; Firm survival; Sweden; Administrative population register data; Administrative firm survival data; Internal and external factors